Unofficial trade when states are weak: the case of cross-border commerce in the Horn of Africa - Peter Little (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
This paper addresses informal cross-border trade in the Horn of Africa, with an emphasis on the Somalia borderlands. It will be shown that despite the collapse of a government in 1991, Somalia's unofficial exports of cattle to Kenya have grown considerably during the past 13 years. It will be argued that while informal exports and imports of animals are illegal in Kenya and Ethiopia, local institutions and agreements allow the trade to function `on the ground' in the absence of official recognition. The paper concludes with a discussion of the policy implications of informal cross-border commerce in regions of weak administrative control. – cattle ; livestock ; Somalia ; markets
Keywords: E26; O17; Q13; L14; 330; Rind; Außenhandel; Schwarzmarkt; Somalia